The Impact Of Betel Nut Consumption On The Level Of Knowledge, Behavior And Hb Levels In Pregnant Women In The Rimba Jaya Health Center - Mulyaningsih, Dwi Erlis; Retnaningtyas, Erma; Muslichah, Miftakhul; dr Miftakul; Hastuti, Tri (Institute Of Computer Science (IOCS), 2025)
The tradition of chewing betel nut is still a tradition in Merauke, South Papua. The use of betel nut for pregnant women can affect hemoglobin levels.. This study aims to determine the effect of education on the impact of betel nut consumption on the level of knowledge, behavior and Hb levels in pregnant women in the Rimba Jaya Health Center Work Area. Quasi-experimental research design with One Group Pretest-Posttest. With a purposive sampling technique, a sample of 30 respondents, the independent variable is Education and the dependent variable is Knowledge, Behavior and HB Levels in pregnant women. A linear regression statistical test was used. The results of the study from 30 respondents were obtained, namely 30 respondents / all respondents had good knowledge after education (100%), most respondents did not consume betel nut after education as many as 29 respondents (96.7%) and most respondents with the criteria of not being anemic as many as 29 respondents (99.7%). There is an effect of education on knowledge, behavior of betel nut consumption and hemoglobin levels of pregnant women in the Rimba Jaya Health Center work area. The habit of consuming betel nut is a habit that should be changed by pregnant women, as it increases the risk of anemia in pregnant women